Routledge handbook of tourism and hospitality education - Dredge, Dianne; Airey, D. W.; Gross, Michael J. (Routledge, 2015)
"Tourism is much more than an economic sector, it is also a social, cultural, political, and environmental force that drives societal change. Understanding, responding to, and managing this change will inevitably require knowledge workers who are able to address a range of problems associated with tourism, travel, hospitality, and the increasingly complex operating environment within which they exist. The purpose of this Handbook is to provide an insightful and authoritative account of the various issues that are shaping the higher educational world of tourism, hospitality and events education and to highlight the creative, inventive and innovative ways that educators are responding to these issues. It takes as its central focus a dynamic curriculum space shaped by internal and external factors from global to local scales, a variety of values and perspectives contributed by a range of stakeholders, and shifting philosophies about education policy, pedagogy and teaching practice. A benchmark for future curriculum design and development, it critically reviews the development of conceptual and theoretical approaches to tourism and hospitality education. The Handbook is composed of contributions from specialists in the field, is interdisciplinary in coverage and international in scope through its authorship and content. Providing a systematic guide to the current state of knowledge on tourism and hospitality education and its future direction this is essential reading for students, researches and academics in Tourism, Hospitality, Events, Recreation and Leisure Studies"--